Peran Teknologi Informasi Untuk Peningkatan Kemampuan Siswa Smk Dalam Menghadapi Perkembangan Era Digital SMK Negeri 3 Kota Bengkulu - Ricky Zulfiandry; Feri Hari Utami; Venny Novita Sari; Jhoanne Fredericka; Rupawan Azzahra (Jurnal Dehasen Untuk Negeri, 2023)
In the digital era, the role of information technology is needed to face competition in society. Information and communication technology is an important element in contributing to fundamental changes in the structure of operations and organizational management, education, transportation, health, online learning is a teaching and learning process that utilizes the internet and digital media in delivering material. The online learning method is considered closer to the current generation of students who are known to be very integrated with technology products. This is a form of digitalization in the world of education which has many benefits. Today's increasingly sophisticated digital technology causes major changes in the world. Humans have been facilitated in accessing information in many ways, and can freely enjoy the facilities of digital technology, but the negative impacts also appear as threatening. Crime is easy to facilitate, online games can damage the mentality of the younger generation, pornography and copyright infringement are easy to do, and other businesses that are already operating digitally or can evolve to online business can quickly survive amidst a sudden pandemic. while giant companies that could not adapt immediately fell even to the point of stopping production.